Discourses on homosexuality and the paradox of the closet in The New Life (2023) by Tom Crewe - Ayuningtyas, Paramita; Tambunan, Shuri Mariasih Gietty; Saraswati, Asri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This article offers a critical examination of Tom Crewe's biographical novel The New Life (2023), focusing on its representation of homosexual subjectivity in Victorian England—a historical context defined by restrictive moral norms and punitive legal regimes that criminalised same-sex relationships. Drawing on Michel Foucault's theory of discursive power, Eve Kosofsky Sedgwick's concept of the closet, and Michael Boucai's topology of the closet, the study demonstrates that the novel portrays the closet not merely as a private site of concealment but as a complex social mechanism shaped by legal regulation, gender norms, and class-based power relations. Building on this theoretical framework, the article extends Sedgwick's notion of the closet by conceptualising it as a performative and ongoing practice of negotiation, continuously conditioned by specific social and historical contexts. The analysis further argues that marriage, masculinity, and middle-class respectability operate simultaneously as forms of protection and constraint, generating ethical tensions and uneven distributions of vulnerability, particularly along gendered lines. By foregrounding the paradoxical dynamics of the closet, this study contributes to queer literary criticism and biographical fiction studies, demonstrating how The New Life reimagines marginalised historical experiences while also exposing the limits of progressive discourse within enduring heteronormative social structures.